Culture Negative Stent Infection in an Infant with Hypoplastic Left Heart and Persistent Fever. (8th September 2015) - Piggott, Kurt D.; Laham, Federico; Jordan Villegas, Alejandro; Fakioglu, Harun; Blanco, Carlos; Suguna Narasimhulu, Sukumar
Abstract : We present an infant with hypoplastic left heart with persistent fever despite two courses of antibiotics and repeatedly negative blood cultures. He eventually underwent surgical extraction of two stents. The stent cultures became positive; he was treated with 4 weeks of antibiotics and the fever resolved.